Residents' Support for Sports Events Tourism Development in Beach City: The Role of Community's Participation and Tourism Impacts. (April 2019) - Boonsiritomachai, Waranpong; Phonthanukitithaworn, Chanchai
This study aims to explore community participation in shaping their support for the development of sports events tourism. As a part of this investigation, the factors affecting local residents' support of the development of sports events tourism was explored using the triple-bottom-line approach for tourism impacts, thus focusing on socio-cultural, economic, and environmental factors. According to the theoretical framework adopted in this work, residential participation influences their perceptions of tourism impacts and in turn their support for tourism development. This assertion was tested through a survey of Bangsaen residents, as this beach city in Chonburi is a major tourist destination in Thailand. The survey data were subjected to structural equation modelling, revealing that all factors comprising the triple-bottom-line approach exert direct impact on the residents' support for sports events tourism development, which is unaffected by community participation. These findings can provide local authorities, developers, and organizers with guidelines on how to improve local residents' support for sports events tourism.